Palynological and geochemical data from Lake Vouliagmeni, Greece - Andreas Koutsodendris; Achim Brauer; Oliver Friedrich; Rik Tjallingii; Victoria Putyrskaya; Barbara Hennrich; Robert Kühn; Eckehard Klemt; Jörg Pross (PANGAEA, 2023)
Palynological (pollen and dinoflagellate cysts) and geochemical (X-Ray fluorescence [XRF], radionuclides, loss on ignition [LOI]) data from Lake Vouliagmeni, Greece, were generated to reconstruct climate and environmental changes in SE Europe during the past 300 years. The analyses were carried out on five cores recovered from the deepest part of the lake at a water depth of ~49 m, with coordinates between 38° 1 extquotesingle 33 – 38° 1 extquotesingle 43 extquotesingle extquotesingle N and 22° 52 extquotesingle 49 extquotesingle extquotesingle– 22° 53 extquotesingle 14 extquotesingle extquotesingle E. A total of 36 palynological samples, were prepared using standard palynological techniques including freeze-drying, weighing, spiking with Lycopodium spores (Batch Nr. 3140) treatment with HCl and HF, sieving (10 μm), and mounting of the residues on glass slides using glycerin jelly. The XRF core scanning for the elements Si, S, Cl, K, Ca, Ti, Mn, Fe, Br, and Sr was performed with an ITRAX core scanner equipped with a chromium X-ray tube at 200 μm step size, 30 kV tube voltage, 30 mA tube current, and a counting time of 10 s. To minimize sample-geometry effects related to differences in water content, surface irregularities, and sediment density, raw-element intensities (cps) were normalized by center-log-ratio (CLR) transformation. Radionuclide dating was carried out on 1 cm thick samples following freeze-drying, homogenization and placement in cylindrical transparent polystyrene containers that were sealed with an aluminum-composite foil in order to keep the samples Radon-tight. The activity concentrations of the radionuclides were measured gamma-spectrometrically after at least 3 weeks using Canberra-Eurisys Broad Energy Germanium (BEGe-5030) detectors. The activity concentrations were calculated with the LabSOCS (Canberra) calibration software taking into account the self-absorption of γ-rays in both samples and beakers as well as the summation-effects due to simultaneous emissions of several gammas from one nuclear decay. Measuring time was up to 24 h per sample until counting uncertainties of <5 % were achieved. The organic-matter content was determined by measuring loss on ignition (LOI). Bulk samples were freeze-dried for 24 h, and 1 g of the dried, homogenized sediment was dry-ashed at 550 °C for 4 h and subsequently weighed. The weight lost was used to estimate the organic-matter content of the sample (LOI550).